PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI YANG DIKONTROL OLEH MASA KERJA TERHADAP TURNOVER INTENTION PT NET ARTIDAYA - Handaru, Agung Wahyu; Juniarti, Yohana Yohana; Mardiyati, Umi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purposes of this research are 1) to know description of job satisfaction, organizational commitment, working period, and turnover intention 2) test empirically influence of job satisfaction toward turnover intention 3) test empirically influence of job satisfaction controlled by working period toward turnover intention 4) test empirically influence of organizational commitment toward turnover intention 5) test empirically influence of organizational commitment controlled by working period toward turnover intention 6) test empirically influence of job satisfaction and organizational commitment toward turnover intention, and 7) test empirically influence of job satisfaction and organizational commitment controlled by working period toward turnover intention. The object of analysis is employees of PT NET Artidaya using simple random sampling method. The data was collected by using questionnaire and cultivated. The result of t test for job satisfaction is an effect between job satisfaction toward turnover intention. The result of F test for job satisfaction controlled by working period there is an effect between job satisfaction controlled by working period toward turnover intention. The result of t test for organizational commitment there is an effect between organizational commitment toward turnover intention. Keywords: job satisfaction, organizational commitment, working period, turnover intention